A mediação do SINAES no processo de avaliação das bibliotecas universitárias em Fortaleza - Guerra, Maria Aurea Montenegro Albuquerque (2012)
The aim of this work is to analyze the process of evaluation of the universitarian libraries of Fortaleza (Ceará, Brazil) accomplished by INEP/MEC. Here is, also, a brief trajectory of the evaluation of higher education in Brazil, showed under the context of the neo-liberal politics. As internal scenery, it is observable the ways of articulation of the universitarian library of the private instance with the dimensions of physical structure and pedagogical activities. It is intended to establish lines of connection between the instrument of SINAES and the effectiveness of the library in the evaluative process determined by INEP/MEC. Before this reality, the analysis focused on the understanding of INEP evaluators, the managers of private institutions and the librarians. The used methodology is based on fieldwork and the data was analyzed under the perspective of the Discourse Analysis of the Collective Subject, which is based on the opinion of the actors involved in the role of the library in the institutional panorama. The achievements point the universitarian library at a fragile position in the private colleges, having disparity between the featured concepts for this unity of information. It concludes also that the subjectivity, by the part of the evaluators, is constant in the libraries‟ processes of evaluation. Also can be said that the understanding of what is evaluated is not uniform and the insertion of this unity of information in the processes of teaching-learning is still incipient.